Regional discrimination of Agaricus bisporus mushroom using the natural stable isotope ratios. (30th October 2018) - Chung, Ill-Min; Han, Jae-Gu; Kong, Won-Sik; Kim, Jae-Kwang; An, Min-Jeong; Lee, Ji-Hee; An, Yeon-Ju; Jung, Mun Yhung; Kim, Seung-Hyun
Highlights: Accurate proof of geographical origin is important in the global mushroom trade. Stable isotope ratio analysis was used to verify Agaricus bisporus origins. Chemometric approaches were used to find isotopic markers of A. bisporus origin. These methods distinguished between A. bisporus grown in various regions of Korea. This approach should be applicable to other mushroom types and cultivation regions. Abstract: This study was aimed to verify the regional traceability of Agaricus bisporus mushroom using unique δ 13 C, δ 15 N, δ 18 O, and δ 34 S features combined with chemometric approaches. Ten cultivars from 15 mushroom farms in six regions of Korea were measured their isotopic signatures by stable isotope ratio mass spectrometer. The δ 13 C, δ 15 N, δ 18 O, and δ 34 S values were significantly different among mushrooms collected from six cultivation regions ( P  < 0.05). Multi-dimensional plots including the δ 15 N and δ 34 S values demonstrated clear regional discrimination of the Saedo and Saehan cultivars produced from Buyeo, Nonsan, Eumseong, Boryeong, or Gyeongju. Partial least-squares discriminate analysis models showed good discrimination for Saedo (Rx 2  = 0.798 and Q 2  = 0.563) and Saehan (Rx 2  = 0.819 and Q 2  = 0.894). These preliminary results can extend knowledge of regional isotope signatures in A. bisporus mushroom produced in Korea, contributing to accurate geographical authenticity with potential broader applications for the international mushroom market.